Examining Leadership With American Counseling Association Presidents: A Grounded Theory of Leadership Identity Development. (11th September 2018) - Gibson, Donna M.; Dollarhide, Colette T.; Moss, Julie M.; Aras, Yahyahan; Mitchell, Thomas
Abstract : In a grounded theory study, the authors examined the leadership identity development of 12 past presidents of the American Counseling Association. Using individual interviews, the authors identified 3 interactional themes that form a theoretical framework for leadership identity development: (a) influence, motivation, and support to lead; (b) leadership skills; and (c) reinforcing experiences. Implications for counselors and counselor educators are offered.